Makna Sakramen Baptisan dan Perjamuan Kudus bagi Orang Kristen (International Forum of Researchers and Lecturers, 2025)
The sacraments of baptism and the Lord’s Supper are the two main sacraments in the Christian tradition, both carrying profound theological and spiritual significance. A sacrament contains two essential elements: an outward sign (such as water, bread, and wine) and a spiritual reality (namely, the grace of God given through the sign). A sacrament is not merely a symbol, but a means of communion with Christ that strengthens faith and bears witness to God’s grace. In Christian theology, a sacrament is broadly defined as a rite or religious ceremony performed to symbolize or help bring about a transformation in the lives of those who participate in it. The Sacrament of the Lord’s Supper is one of the key sacraments in the Christian tradition, symbolizing the fellowship of believers with Christ through the shared consumption of bread and wine. Its meaning is profound, as it is not only a remembrance of Jesus Christ’s sacrifice on the cross, but also an expression of faith and a deep reflection on the saving love of God. The Lord’s Supper also contains an eschatological meaning, pointing believers toward the future. In each celebration of the Lord’s Supper, the people of Christ anticipate the heavenly banquet at the end of the age.